Norbornene chaotropic salts as low molecular mass ionic organogelators (LMIOGs) - Gunnlaugsson, Thorfinnur; Engstrom, Jordan R.; Savyasachi, Aramballi J.; Parhizkar, Marzieh; Sutti, Alessandra; Hawes, Chris S.; White, Jonathan M.; Pfeffer, Frederick M. (My University, 2018)
Phenylalanine functionalised norbornene (9:Na) functions as a potent, low molecular-mass (MW = 333 Da) ionic organogelator with a minimum gelating concentration of 0.5 wt% in THF, i-PrOH, 1,4-dioxane and n-BuOH. Fibrous crystals form in the gel and X-ray crystallography identified a cation mediated helical assembly process controlled by the chirality of the phenylalanine. In addition to excellent gelating properties 9:Na readily forms aqueous biphasic and triphasic systems.
Keywords: organogelating agents; Low molecular mass ionic organogelators; Organogels